2007
DOI: 10.1159/000111759
|View full text |Cite
|
Sign up to set email alerts
|

S-Ibuprofen Effectively Inhibits Thromboxane B<sub>2</sub> Levels and Platelet Function in an Experimental Model of Lipopolysaccharide-Stimulated and Non-Stimulated Whole Blood

Abstract: Objective: The present study aimed at testing the effect of S- and R-ibuprofen on thromboxane B2 (TXB2), collagen-epinephrine closure time (CEPI-CT) and collagen-adenosine 5′-diphosphate closure time (CADP-CT) in lipopolysaccharide (LPS)-stimulated and non-stimulated human whole blood. Materials and Methods: Whole blood was incubated with S- or R-ibuprofen with and without prior stimulation with LPS. To verify ibuprofen’s potential effects on TXB2, varying ratios of concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…TXA 2 is released during myocardial ischemia and the level is proportional to the number of arrhythmias that occur (Coker et al, 1981;Hirsh et al, 1981). In addition, TXA 2 is released by inflammatory cytokines (Takayama et al, 2005;Kaehler et al, 2008). It is possible that endogenous TXA 2 that is released during tissue damage or inflammation induces direct effects on the heart in addition to the indirect actions caused by platelet aggregation and vasoconstriction.…”
Section: Discussionmentioning
confidence: 99%
“…TXA 2 is released during myocardial ischemia and the level is proportional to the number of arrhythmias that occur (Coker et al, 1981;Hirsh et al, 1981). In addition, TXA 2 is released by inflammatory cytokines (Takayama et al, 2005;Kaehler et al, 2008). It is possible that endogenous TXA 2 that is released during tissue damage or inflammation induces direct effects on the heart in addition to the indirect actions caused by platelet aggregation and vasoconstriction.…”
Section: Discussionmentioning
confidence: 99%
“…The S(+)-enantiomers are responsible for beneficial and adverse effects [139]. S(+)-Ibuprofen, S(+)-ketoprofen and S(+)naproxen are more effective in inhibiting human platelet aggregation and suppressing human platelet prostaglandin production than R(-)ibuprofen [140], R(-)-ketoprofen [141] and R(-)naproxen [142], respectively.…”
Section: Stereostructure Specificity and Membrane Interactivitymentioning
confidence: 99%
“…Furthermore, possible adverse effects, which might be mediated by the R -enantiomer, could be minimized while keeping the risk of cardiovascular events as low as possible [10] . Indeed an in vitro study showed that in clinically relevant concentrations the R -enantiomer may exert a prothrombotic effect by enhancing thromboxane B 2 levels under lipopolysaccharide-stimulated conditions [15] . Several clinical trials and postmarketing surveillance studies were performed to broaden the findings on dexibuprofen.…”
mentioning
confidence: 99%